Removal of Zn2+ from Aqueous Solution using Castor Seed Hull - Mohammod, M.; Sen, Tushar; Maitra, S.; Dutta, B. (Springer Netherlands, 2011)
The effects of various experimental parameters on adsorption of Zn2+ metal ion from its aqueous solution by castor seed hull and also by activated carbon have been investigated using batch adsorption experiments. It has been found that the amount of zinc adsorbed per unit mass of the hull increases with the initial metal ion concentration, contact time, solution pH and with the amount of the adsorbent. Kinetic experiments clearly indicate that adsorption of zinc on both castor hull and activated carbon is a three-step process—a rapid adsorption of the metal ion, a transition phase, and an almost flat plateau. This has also been confirmed by the intraparticle diffusion model. It has also been found that the zinc adsorption process followed pseudo-second order kinetics. The kinetic parameters including rate constants have been determined at different initial metal ion concentration, pH, amount, and type of adsorbent, respectively. The Langmuir and Freundlich adsorption isotherm models have been used to interpret the equilibrium adsorption data. The Langmuir model yields better correlation coefficients. The monolayer adsorption capacities (q m ) of castor hull and activated carbon have been compared with those for others reported in the literature. The value of separation factor (R L ) derived from the Langmuir model gives an indication of favorable adsorption.Finally, from comparative studies, it has been found that castor hull is a potentially attractive adsorbent as compared to commercial activated carbon for the removal of zinc from aqueus effluents.